1979
DOI: 10.1042/cs057325s
|View full text |Cite
|
Sign up to set email alerts
|

Intralymphocytic Sodium in Hypertensive Patients: A Significant Correlation

Abstract: 1. Intralymphocytic sodium concentration was measured in 50 patients with essential stable hypertension, 44 patients with labile hypertension and 40 subjects with normal blood pressure. 2. Intralymphocytic sodium concentration in normotensive subjects was significantly lower than in the other two groups. 3. The concentration was significantly correlated with mean blood pressure in the group as a whole and in the groups with stable and with labile hypertension. No correlation was found in normal subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1981
1981
1995
1995

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Since 1960 in several studies elevated intracellular Na + levels have been found in red blood cells and in other blood cells from essential hypertensive patients [1,2,4,5,[7][8][9]11]. The overlap between the ranges of hypertensive and normotensive patients, which was often described, may be due to the occurrence of several entities within the unprecisely defined group of essential hypertensives.…”
Section: Introductionmentioning
confidence: 98%
“…Since 1960 in several studies elevated intracellular Na + levels have been found in red blood cells and in other blood cells from essential hypertensive patients [1,2,4,5,[7][8][9]11]. The overlap between the ranges of hypertensive and normotensive patients, which was often described, may be due to the occurrence of several entities within the unprecisely defined group of essential hypertensives.…”
Section: Introductionmentioning
confidence: 98%
“…The effect of this factor is probably accompanied by an increase in the intracellular concentration of sodium ions in blood cells [3,11], and this increased sodium content may lower the affinity of the [32-adrenoceptors and coupled AC for catecholamine stimulation [8]. Along with this, studies of ouabain suggest that the Na,K-ATPase inhibitor is able to reduce AC sensitivity to sodium ions in a manner which is not yet understood.…”
Section: Resultsmentioning
confidence: 99%
“…Progression of the disease is attended by a decrease in adenylate cyclase (AC) affinity to catecholamines in peripheral blood lymphocytes [8] and a rise in the intracellular concentration of sodium ions in erythrocytes and lymphocytes [3,11]. Interaction of a-and [3-adrenergic receptors with ligands is modulated allosterically by monovalent cations (Na+>Li+>K+), while changes in the receptor affinity to catecholamines correlate with the changes in the intraeellular sodium concentration [10,12,13].…”
mentioning
confidence: 99%
“…Evidence for the existence of the membrane abnormality in these cells comes mainly from studies of human essential hypertension. Ambrosioni et al 14 have reported an increased lymphocyte sodium content in patients with essential hypertension as compared with that in normotensive controls. Pedersen et al 15 ascribe a higher sodium influx in the lymphocytes from normotensive patients with a family history of hypertension to enhanced sodium-lithium countertransport and unidirectional net sodium flux.…”
mentioning
confidence: 99%